Decreased paraoxonase activity in critically ill patients with sepsis - Novak, Frantisek; Vavrova, Lucie; Kodydkova, Jana; Novak, Frantisek; Hynkova, Magdalena; Zak, Ales; Novakova, Olga (Clinical and experimental medicine, 2010)
Paraoxonase 1 is believed to play a role in preventing lipid oxidation and, thus, limiting production of proinflammatory mediators. Systemic inflammatory response in sepsis increases oxidative stress and decreases high-density lipoprotein (HDL) concentrations. The objective of this study was to investigate serum paraoxonase 1 activities in critically ill patients with sepsis and after recovery. Serum paraoxonase 1 arylesterase/paraoxonase activities, concentration of total cholesterol, HDL cholesterol (HDL-C) and serum C-reactive protein (CRP) in septic patients of a medical intensive care unit (n = 30) and age/sex-matched outpatient controls without sepsis (n = 30) were analyzed. Paired convalescent samples were also taken 1 week after recovery (n = 11). In septic patients, both arylesterase (88.3 +/- 36.5 vs. 162.1 +/- 44.8 kU/l, P < 0.001) and paraoxonase (75.2 +/- 50.0 vs. 125.2 +/- 69.4 U/l, P < 0.01) paraoxonase 1 activities decreased as compared to controls. Both activities normalized after recovery. Negative correlation was found between CRP and both arylesterase (r = -0.676, P < 0.001) and paraoxonase (r = -0.401, P < 0.01) as well as positive correlation between HDL-C and both arylesterase (r = 0.585, P < 0.001) and paraoxonase (r = 0.405, P < 0.01) paraoxonase 1 activities. The decreased activity of paraoxonase 1 in negative correlation with CRP offers a potentially useful marker of sepsis progress and recovery in critically ill patients.
Keywords: Male; biologické markery; HDL-cholesterol; Biomarkers; Cholesterol, HDL; sepse; Critical Illness; Cholesterol; Adult; C-reaktivní protein; Aged; dospělí; mužské pohlaví; senioři; Sepsis; cholesterol; Aryldialkylphosphatase; lidé; kritický stav; ženské pohlaví; Humans; aryldialkylfosfatasa; C-Reactive Protein; Female; lidé středního věku; Middle Aged